2020
DOI: 10.1111/all.14234
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use during pregnancy increases offspring asthma severity in a dose‐dependent manner

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 37 publications
3
52
0
Order By: Relevance
“…Therefore, by inducing reduction and modification of the infant intestinal microbiota, early pregnancy antibiotic exposure may influence on immunological development, leading to an increase of the potential of chronic disease 42,53 . In an animal study, maternal vancomycin treatment during pregnancy increased offspring allergic lung inflammation 54 . Milliken et al 55 reported that maternal use of antibiotics during the antenatal or labor could cause intestinal dysbiosis and particularly reduced diversity of Lactobacillus and Bifidobacterium .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, by inducing reduction and modification of the infant intestinal microbiota, early pregnancy antibiotic exposure may influence on immunological development, leading to an increase of the potential of chronic disease 42,53 . In an animal study, maternal vancomycin treatment during pregnancy increased offspring allergic lung inflammation 54 . Milliken et al 55 reported that maternal use of antibiotics during the antenatal or labor could cause intestinal dysbiosis and particularly reduced diversity of Lactobacillus and Bifidobacterium .…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary microbial dysbiosis can influence the inflammation status of the host. The dysbiosis can be inherited, if the mother was treated with antibiotics during the pregnancy resulting in higher asthma rates in the offspring as shown by Alhasan et al 57 Surprisingly, instead of the expected upregulation of type 2 cytokines in allergic offspring, a downregulation was found. Causalities are still unclear and will require specifically designed future studies to address this issue.…”
Section: Microbial Dysbiosis and Asthmamentioning
confidence: 96%
“…22 The use of antibiotics by mothers during pregnancy increases the risk of asthma in their offspring. 23 Hence, some asthma-related immune markers in mothers and their offspring were examined in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal immune homeostasis is affected by the composition of the symbiotic microbial community, 21 and the mother's microbial environment may affect the early formation of the fetal immune system 22 . The use of antibiotics by mothers during pregnancy increases the risk of asthma in their offspring 23 . Hence, some asthma‐related immune markers in mothers and their offspring were examined in mice.…”
Section: Discussionmentioning
confidence: 99%